2019
DOI: 10.1093/cercor/bhz094
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI Analyses of Regional Brain Growth in Living Fetuses with Down Syndrome

Abstract: Down syndrome (DS) is the most common liveborn autosomal chromosomal anomaly and is a major cause of developmental disability. Atypical brain development and the resulting intellectual disability originate during the fetal period. Perinatal interventions to correct such aberrant development are on the horizon in preclinical studies. However, we lack tools to sensitively measure aberrant structural brain development in living human fetuses with DS. In this study, we aimed to develop safe and precise neuroimagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
44
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 40 publications
7
44
0
Order By: Relevance
“…Guidi et al, (2018) have reported a comparable number of GFAP-labelled astrocytes and reduced number of neurons, suggestive of increased percentage of astrocytic cells (< 21GW), in the fusiform and inferior temporal gyrus [ 18 ]. We did not assess neuronal number in this study, but the decreased number of SOX2 cells in the oSVZ of DS and observed decreases in cortical volumes from fetal MRI studies could reflect decreased neuronal numbers observed in the cortex of the DS brain after birth [ 14 , 45 , 50 , 55 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guidi et al, (2018) have reported a comparable number of GFAP-labelled astrocytes and reduced number of neurons, suggestive of increased percentage of astrocytic cells (< 21GW), in the fusiform and inferior temporal gyrus [ 18 ]. We did not assess neuronal number in this study, but the decreased number of SOX2 cells in the oSVZ of DS and observed decreases in cortical volumes from fetal MRI studies could reflect decreased neuronal numbers observed in the cortex of the DS brain after birth [ 14 , 45 , 50 , 55 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…The neurodevelopmental phenotype is variable and associated with cognitive deficits and impairments in speech, motor and language functions. Whilst the neurological phenotype of DS changes over a lifetime, smaller whole brain volumes, predominantly in the cortex and cerebellum, have been observed in early fetal life [19,45,55]. Structural magnetic resonance imaging (MRI) studies show that the cortex develops with a simplified gyral appearance (less folded), reduced overall cortical surface area and volume, and abnormal cortical thickness in children and young adults with DS [33,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original differences in gross measurements in the trisomic embryos from the 1924 2007 analysis were thought to be derived from changes in the expansion of the developing pallial wall, similar to how changes in the developing cortical wall may underlie the later microencephaly in humans with DS (Tarui et al, 2020). In particular, the 1924 2007 cohort displayed a significantly smaller thickness of the total pallium from E13.5 to E16.5 in the trisomic embryos compared to the euploid controls (Chakrabarti et al, 2007).…”
Section: Embryonic Pallial Thickness Measurementsmentioning
confidence: 99%
“…Identification of neural differences much earlier in the life course in DS, could potentially offer opportunities for more effective intervention. We and others have recently demonstrated that fetuses and neonates with DS have reduced whole brain, cortical and cerebellar volumes from as early as 20 weeks gestational age (GA), using in vivo volumetric MRI (Tarui et al, 2019;Patkee et al, 2020). Whether such anatomical differences are accompanied by early differences in the metabolite levels, that reflect neuronal and glial function, and alter neurodevelopmental outcome, remains unknown.…”
Section: Introductionmentioning
confidence: 99%